Low Stroke Risk in Children With Sickle Cell Disease in French Guiana: A Retrospective Cohort Study - Gargot, Julie; Parriault, Marie-Claire; Adenis, Antoine; Clouzeau, Jérôme; Dinh Van, Kim-Anh; Ntab, Balthazar; Defo, Antoine; Nacher, Mathieu; Elenga, Narcisse (Frontiers in Medicine, 2022)
One in every 227 babies born in French Guiana has sickle cell disease, which represents the greatest incidence in France. This study aimed to determine the incidence of stroke in children with sickle cell disease and its associated risk factors. This retrospective cohort study included all children with sickle cell disease diagnosed in the neonatal period who were born in French Guiana between 01/01/1992 and 12/31/2002. Of a total of 218 records, 122 patients were included. There were 70 HbSS/ Sβ0 (58%), 40 HbSC (33%), and 11 Sβ+ thalassemia (9%). The number of emergency admissions was significantly different between genotypes, with a higher number in SS / Sβ0 children (p=0.004). There were significantly more acute chest syndromes (p=0.006) and more elevated Lactate Dehydrogenase in SS/Sβ0 patients (p=0.003). Three of these patients had ischemic strokes at a mean age of 6,9 years, and one had a haemorrhagic stroke at the age of 9,2 years. The incidence rate of ischemic stroke for SS/Sβ0 children was 3,1 (95% CI: 1,0 - 9,7) per 1000 patient-years, and the clinically apparent stroke risk by the age of 15 years and 3 months was 6,4%. The incidence of hemorrhagic stroke was 1,1 (95% CI: 0,1 – 7,4) per 1000 patients-years. No patient with SC or Sβ+ thalassemia genotypes experienced any stroke.